Influência das variações da temperatura na produção de biogás em biodigestores modelo Bioköhler protegido com estufa plástica - Soares, Caroline Monique Tietz (2016)
The anaerobic digestion process has been applied for the treatment of effluents both in developed countries as well as underdeveloped countries. Amongst the most predominant factors that affect the efficiency of this process is the temperature, considering the microorganisms development and the biogas production constitutes the temperature biodigester operational function. This study aimed at verifying the influence of temperature variation in the production of biogas from dairy cattle manure, in a Bioköhler biodigester covered with greenhouse plastic film. The experiment was performed in a 20 m3 biodigester located in the Antonio Carlos dos Santos Pessoa Experimental Station belonging to UNIOESTE Marechal Cândido Rondon Campus, during the period between 08/03/2014 to 02/07/2015. Data from the internal biodigester temperature and the greenhouse was obtained in conjunction with the external biodigester temperature, affluent and effluent density, total solid values, fixed and volatile, biogas volume produced and the concentration of CH4 present in this biogas. The results indicated that the microorganisms acted in the mesophilic layer and there was the indication that the production of biogas was influenced by temperature variability, nevertheless, the greenhouse avoided sudden alterations at this temperature. The results also evidenced that the medium capacity expected in the production of biogas surrounded 12 m3 per day and came across with an average of 57,33% of CH4 in this biogas. There was satisfactory volatile solid removal